Analysis Of Appropriate Employment Benefits With Psak 24 On PT. Tri Starmandiri - Muhammad Mursalim; Syamsuddin, Syamsuddin; Asriani Hasan (CV. AFDIFAL MAJU BERKAH, 2024)
This study aims to find out how the application of employee benefit accounting at PT. Tri Star Independent. Researchers took the object of research at PT. Tri Star Independent. The data analysis method used is qualitative analysis with a descriptive approach. This research data is obtained from primary and secondary data. Data collection techniques in the form of literature research and field research are direct interviews with the company, namely the head of the finance room. The results of research at PT. Tri Star Mandiri can be concluded that the benefits of employment at PT. Tri Star Mandiri can be categorized into four categories based on PSAK 24, namely short-term employee benefits, postemployment benefits, long-term benefits and severity pay for termination of employment contracts. Of the four employee benefits, only short-term employee benefits applied are in accordance with PSAK 24. While the other three employee benefits, namely post-employment benefits, long-term benefits, and severity pay, are only post-employment benefits for defined benefit programs applied and are in accordance with PSAK 24 while defined contribution programs are not applied and long-term employee benefits, severance has not been applied so it does not need to be adjusted to PSAK 24.